2002
DOI: 10.1046/j.1464-410x.2002.02710.x
|View full text |Cite
|
Sign up to set email alerts
|

Microangiographic imaging of the prostate

Abstract: Objective To present the results of microangiography in visualizing prostatic microvascularization. Materials and methods A contrast medium was injected into the vessels of prostate specimens obtained during surgery, to fill small vessels; nine specimens were obtained after cystoprostatectomy and two after radical prostatectomy. Branches of prostatic or seminal vesicle arteries were used for the injection, the specimens then fixed in formalin, sectioned and X-rayed. Results In five samples the quality of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The capsular arteries were found to perforate the capsule at approximately the 2 and 10 o'clock positions for the anterior-lateral branches and at the 5 and 7 o'clock positions for the posterior-lateral branches, as previously reported [11][12][13][14].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The capsular arteries were found to perforate the capsule at approximately the 2 and 10 o'clock positions for the anterior-lateral branches and at the 5 and 7 o'clock positions for the posterior-lateral branches, as previously reported [11][12][13][14].…”
Section: Discussionsupporting
confidence: 78%
“…These inferior branches may have anastomoses with perineal branches of the internal pudendal artery and with the middle rectal or anal arteries [10]. After reaching the prostate the main source of prostatic microvascularisation are 3 groups of arteries (capsular, intermediate and periurethral) [11]. The capsular branches are arranged on the surface in a posterior and anterior group with anterolateral and posterolateral subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Also, more than one PA may be found in as many as 30% of pelvic sides (10). After reaching the prostate, the PAs have a corkscrew appearance (7,8) and perforate the capsule in four quadrants, two anterior/lateral for the cranial PAs and two posterior/lateral for the caudal PAs (11)(12)(13).…”
mentioning
confidence: 99%
“…Previous studies have confirmed that BPH induces neovascularisation, and the main sources of blood supply of prostate are capsular vessels passing the urethra at the 1, 5, 7 and 11 o'clock positions, especially in the 5 and 7 o'clock positions. A large proportion of the capillaries run under the capsule, and then mostly run towards the urethra concentrically [19]. The TZ gland was the predilection site of BPH and had a rich blood supply, resulting in the highest enhancement on CEUS imaging.…”
Section: Discussionmentioning
confidence: 99%